A column of fire [compact disc, unabridged] - Follett, Ken (Follett, Ken. Kingsbridge., 2017)
In 1558, the ancient stones of Kingsbridge Cathedral look down on a city torn apart by religious conflict. As power in England shifts precariously between Catholics and Protestants, high principles clash bloodily with friendship, loyalty, and love. Ned Willard wants nothing more than to marry Margery Fitzgerald. But when the lovers find themselves on opposing sides of the religious divide sweeping across the country, Ned goes to work for Princess Elizabeth. When she becomes queen, all Europe turns against England. The shrewd, determined young monarch sets up the country's first secret service, to give her early warning of assassination plots, rebellions, and invasion plans. Over a turbulent half century, the love between Ned and Margery seems doomed as extremism sparks violence from Edinburgh to Geneva. Elizabeth clings precariously to her throne and her principles, protected by a small, dedicated group of resourceful spies and courageous secret agents.